The age distribution of business firms - Flavio Calvino; Daniele Giachini; Mattia Guerini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2020)
We investigate upon the shape and the determinants of the age distribution of business firms. By employing a novel dataset covering the population of French businesses, we highlight that a geometric law provides a reasonable approximation for the age distribution. However, relevant systematic deviations and sectoral heterogeneity appear. We develop a stochastic model of firm dynamics to explain the mechanisms behind this evidence and relate them to business dynamism. Results reveal a long-term decline in entry rates and lower survival probabilities of young firms. Our findings bear important implications for aggregate outcomes, notably employment growth.
Keywords: L11; L22; M13; M21; 330; Firm demographics; age distribution; business dynamism